Pengaruh Tingkat Pengangguran, Indeks Pembangunan dan Pertumbuhan Terhadap Tingkat Kemiskinan di Provinsi Sumatera Utara Tahun 2025 - Depina Br Tumangger; Joko Suharianto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Poverty is a complex problem that continues to be a global challenge, including in Indonesia. This study aims to analyze the factors causing poverty, its impact on society, and the efforts that have been made to address it. Research methods include a literature review, statistical data analysis, and case studies. The results indicate that poverty is caused by various factors, such as lack of access to education, health, employment, and economic resources. Its impacts include health problems, low education, crime, and social instability. The government and various institutions have implemented various efforts, such as social assistance programs, skills training, and infrastructure development, but their effectiveness still needs to be improved. This study concludes that poverty alleviation requires a multidimensional approach involving all parties, with a focus on improving the quality of human resources, creating jobs, and equitable development.